Pengaruh pati ganyong (Cannaedulis, Ker) modifikasi terhadap kualitas kefir (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2014)
The purpose of the research was to determine the effect of using various concentration of modification starch on pH, water content, viscosity and fat content. The research material were kefir made from cow's milk with kefir grains derived from animal product technology laboratory of Animal Husbandry Brawijaya University. The research method was an experimental research with randomized block design. The treatments were the addition of canna starch modification 0% (G0), 0.2% (G1), 0.4% (G2), 0.6% (G3), 0.8% (G4) and 1.0% (G5) of the milk volume. Each treatment was replicated 3 times. The result showed that the addition of modified canna starch provided highly significant effect (p<0.01) on pH, water content, viscosity and fat content. The study concluded that addition of canna starch modification could improve the quality of kefir in terms of pH, water content, and viscosity, protein and lactic acid bacteria. The addition of 1% of canna starch modification had the best kefir quality. Keywords: Kefir, canna starch modification, STTP